Disorders of the Cardiovascular System in Patients with Chronic Viral Hepatitis - M. V. Chistyakova; A. V. Govorin; Yu. V. Parkhomenko (Столичная издательская компания, 2019)
Aim. To study some structural and functional parameters of the heart and the parameters of hepato-lienal blood flow in patients with chronic viral hepatitis (CVH).Material and methods. 74 patients with CVH were examined, the average age was 41 years, the disease duration - 3.6 years. The patients were divided into 2 groups: group 1 - patients with minimal biochemical activity of hepatitis (n=39); group 2 - patients with moderate hepatitis activity (n=35). The control group included 22 healthy patients. Parameters of tissue doppler echocardiography, hepato-lienal blood flow were evaluated depending on the laboratory activity of CVH.Results. The systolic velocity of the fibrous ring displacement of the tricuspid valve in patients of groups 1 and 2 was lower than in the control by 15% and 17%, respectively (p<0.001). Em decreased in groups 1 and 2 in comparison with healthy individuals in the basal segment of the left ventricle lateral wall, on the mitral valve fibrous ring, in the basal segment of the interventricular septum (p<0.001). The Em/Am ratio decreased in patients of groups 1 and 2 compared with healthy patients in the basal segment of the left ventricle lateral wall, in the medial segment of the interventricular septum, on fibrous ring of the tricuspid valve, in the basal and medial segments of the right ventricular lateral wall (p<0.001). Isovolumic contraction and relaxation time as well as the volume index of the left atrium were increased in patients of the 1st and 2nd groups in comparison with control; more severe violations were observed in patients of the 2nd group (p<0.001). In patients of both groups, acceleration of blood flow and dilation of arteries and veins in the hepato-lienal circulation system (p<0.001) were found. Besides, in patients with moderate hepatitis activity there was an acceleration of blood flow in the hepatic artery in comparison with the control (p<0.001).Conclusion. In patients with CVH the follow disorders were observed: decrease in the global longitudinal systolic function of the right ventricle, violation of diastolic relaxation of the ventricles, increase in the volume index of the left atrium, as well as expansion of the arteries and veins of the hepato-lienal circulation system. These violations were more pronounced in patients with a moderate laboratory activity of CVH. Correlations between cardiohemodynamic parameters, indicators of hepato-lienal blood flow and viral load were revealed.